2014
DOI: 10.4103/0972-2327.144044
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in children with cerebral palsy and its correlation with sleep disturbance in primary caregivers and other associated factors

Abstract: Aims:To observe prevalence of sleep disturbance (SD) in cerebral palsy (CP) children in a specific age-group and its correlation with SD in primary caregivers and other associated factors.Materials and Methods:This was a prospective cross-sectional study. SD assessed using Sleep Disturbance Scale for Children (SDSC) in CP children and Pittsburgh Sleep Quality Index (PSQI) in caregivers. Fifty cases of clinically diagnosed CP [27 females, mean age: 107.9 ΁ 29.5 months (range: 78-180 months)] fulfilling criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 19 publications
3
32
0
1
Order By: Relevance
“…An Italian study on pre-school-aged children with CP also had similar results (P=0.146). 12,22 However, a cross-sectional study in Uganda found a significant association (OR 13.182; 95%CI 3.7 to 47.0). 9 No association was found between sleep disorders and intensity of physiotherapy, perhaps because the physiotherapy techniques and methods were not uniform, as subjects used various physiotherapy providers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An Italian study on pre-school-aged children with CP also had similar results (P=0.146). 12,22 However, a cross-sectional study in Uganda found a significant association (OR 13.182; 95%CI 3.7 to 47.0). 9 No association was found between sleep disorders and intensity of physiotherapy, perhaps because the physiotherapy techniques and methods were not uniform, as subjects used various physiotherapy providers.…”
Section: Discussionmentioning
confidence: 96%
“…Disturbed sleep microarchitecture due to no recognizable nocturnal seizure is one of the proposed hypotheses. 22 Sleep disorders in nocturnal seizures can cause decreased REM phase, increased NREM phase 1, and decreased sleep efficiency. Lack of sleep can cause seizures due to interictal epileptiform discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Acredita-se que o nível de comprometimento seja mais relevante para essa análise, o qual abrange áreas não só motora grossa e fina como cognitivas, sensoriais, e demais quadros sintomáticos e contextuais. Adiga et al 29 em um estudo transversal prospectivo para avaliar a presença de distúrbios do sono em crianças com PC e, concomitantemente, tais distúrbios nas mães dessas crianças, assim como, fatores associados a essa condição, verificaram que o grau de comprometimento motor infantil foi insignificante no comprometimento do cuidador.…”
Section: Discussionunclassified
“…Sleep disorders are common in children with neurodevelopmental disabilities (NDDs), with a reported prevalence as high as 86% (Robinson-Shelton & Malow, 2016;Simard-Tremblay, Constantin, Gruber, Brouillette, & Shevell, 2011). In addition to affecting the children's physical and cognitive health and development (Turnbull, Reid, & Morton, 2013), sleep disorders may greatly impact on the well-being of both the children and their families (Adiga, Gupta, Khanna, Taly, & Thennarasu, 2014;Mörelius & Hemmingsson, 2014;Sandella, O'Brien, Shank, & Warschausky, 2011). Therefore, improving the quality of sleep in children with NDDs not only has the potential benefit of improving their clinical outcomes (Owens 2008), it can greatly ameliorate the quality of life of the entire family (McDonald & Joseph, 2019).…”
Section: Introductionmentioning
confidence: 99%